Clinical success rate of percutaneous management in the thrombosed hemodialysis graft at King Chulalongkorn Memorial Hospital - Chatangam, Nisachon; Pincharoen, Nutcha (Chulalongkorn Medical Journal, 2023)
Background : Percutaneous thrombolysis can be the effective method for treatment of the hemodialysis graft. Objective : To retrospectively determine the clinical success rate of percutaneous management in thrombosed hemodialysis graft, the primary and secondary patency periods of graft after percutaneous management and complication at King Chulalongkorn Memorial Hospital from 1 January, 2007 to 30 November, 2014. Materials and Methods : Twenty-nine PTFE grafts in 29 patients were referred to Intervention Radiology Unit for the percutaneous management of thrombosed hemodialysis graft. Angiographic reports and hospital medical records were analyzed for the clinical success rate, procedural record, angiographic finding, complication, and patency period of the graft after treatment. Clinical success rate was determined by complete graft restoration with a palpable thrill and return to normal dialysis for at least one session. Patency period were calculated with Kaplan-Meier method analysis to estimate graft survival probability with standard deviation. Results : Clinical success rate was achieved in 28 of 29 cases (96.55%). Neither major nor minor complication occurred. After successful percutaneous thrombolysis, 3 of 28 were loss to follow up. Consequently, 25 grafts were evaluated for patency periods with the mean follow-up period of 593.6 ± 79.5 days (437.7 - 749.5 days). Mean patency period (mean survival time) after the 1st percutaneous thrombolysis of all 25 grafts were calculated to 263.6 ± 49.4 days (166.9 - 360.7 days). Conclusion : Percutaneous thrombolysis is a safe and effective mean for treatment of thrombosed hemodialysis graft at King Chulalongkorn Memorial Hospital. Our success rate is comparable to the National Kidney Foundation Dialysis Outcome Quality Initiative.